Water balance analysis for the Tonle Sap Lake–floodplain system. Issue 4 (14th February 2013) - Kummu, M.; Tes, S.; Yin, S.; Adamson, P.; Józsa, J.; Koponen, J.; Richey, J.; Sarkkula, J.
Abstract The Tonle Sap Lake of Cambodia is the largest freshwater body of Southeast Asia, forming an important part of the Mekong River system. The lake has an extremely productive ecosystem and operates as a natural floodwater reservoir for the lower Mekong Basin, offering flood protection and assuring the dry season flow to the Mekong Delta. In light of the accelerating pace of water resources development within the Mekong Basin and the anticipation of potentially significant hydrological impacts, it is critical to understand the overall hydrologic regime of Tonle Sap Lake. We present here a detailed water balance model based on observed data of discharges from the lake's tributaries, discharge between Mekong and the lake through the Tonle Sap River, precipitation, and evaporation. The overland flow between the Mekong and lake was modelled with the EIA 3D hydrodynamic model. We found that majority (53.5%) of the water originates from the Mekong mainstream, but the lake's tributaries also play an important role contributing 34% of the annual flow, while 12.5% is derived from precipitation. The water level in the lake is mainly controlled by the water level in the Mekong mainstream. The Tonle Sap system is hence very vulnerable, from a water quantity point of view, to possible changes in the Mekong mainstream and thus, development activities in the whole Mekong basin. From a biogeochemical point of view, the possible changes in the lake's own catchment are equally important, together with the changes in the whole Mekong Basin. Based on our findings, we recommend of continuing the monitoring programmes in lake's tributaries and urgently starting of groundwater measurement campaign within the floodplain, and including the groundwater modelling to be part of the hydrodynamic models applied for the lake. Copyright © 2013 John Wiley & Sons, Ltd.